Hearing Status After Cartilage Augmented Type III Tympanoplasty: In Chronic Otitis Media Squamous Type - Verma, Lok Ram; Paudel, Dhundi Raj (Journal of Nepalgunj Medical College, 2021)
Introduction: Tympanoplasty is typically performed in conjunction with a canal wall down mastoidectomy in patient with Chronic Otitis Media Squamous. The results from experimental and clinical studies of the type III stapes columellar reconstruction have shown that interposing a disk of cartilage between the graft and the stapes head improves hearing in the lower frequencies by 5 to 10 dB. They hypothesize that the cartilage acts to increase the “effective” area of the graft that is coupled to the stapes, which leads to an increase in the middle ear gain of the reconstructed ear. Aims: To assess the hearing improvement after cartilage augmented Type III Tympanoplasty in chronic otitis media squamous disease. Methods: This study was conducted in 44 patients with Chronic Otitis Media squamous in the patients attending the department of Otorhinolaryngology in NGMC teaching hospital from November 2018 to March 2020. Canal Wall Down mastoidectomy with cartilage augmented type III Tympanoplasty and was done. Augmentation was done with thin 3-4 mm conchal cartilage interposed between stapes and Temporalis fascia graft. Results: There were 11(25%) male and 33(75%) female, with mean age of 29.48 years, ranging from minimum of 15 years to maximum 56 years. The preoperative mean A–B gap was 21.82 and postoperatively means AB gap was 12.20 dB with overall AB gap gain was 9.64 dB. Conclusion: Significant hearing improvement is seen in Canal Wall Down mastoidectomy Chronic Otitis Media squamous after cartilage augmented type III tympanoplasty.